The effect of soda immersion on nano hybrid composite resin discoloration - M. Chair Effendi; Yuli Nugraeni; Rizki Widya Pratiwi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Composite resin is the tooth-colored restorative material which most of the people are fond of due to their aesthetic value. The composite resin discoloration may happen because of the intrinsic and extrinsic factors. Soda water is one of the beverages which can cause the composite resin discoloration. Purpose: The study was aimed to determine the effect of soda immersion on nano hybrid composite resin discoloration. Methods: The study was an experimental laboratory study using 100 shade A3 nano hybrid composite resin specimens with the diameter of 5 mm and density of 2mm. The samples were divided into 5 groups, each group was immersed in different beverages. The beverages were mineral water; lemon-flavored soda; strawberry-flavored soda; fruit punch-flavored soda; and orange-flavored soda for 3, 7, 14 and 21 days respectively, in the temperature of 37o C. The discoloration measurement utilizes Spectrophotometer, Vita Easy Shade, and uses CIEL*a*b* method. Results: The result showed that the duration of immersion in soda had an effect on the Nano hybrid composite resin discoloration. Strawberry and fruit punch- flavored soda were the most influential components toward the discoloration. Nevertheless, the generally-occurred discoloration was clinically acceptable (∆E ≤ 3,3). Conclusion: The study suggested that the soda immersion duration has effect on Nano hybrid composite resin discoloration.Latar belakang: Resin komposit adalah material sewarna gigi yang diminati masyarakat karena memiliki nilai estetik yang baik. Perubahan warna resin komposit dapat terjadi karena faktor intrinsik dan ekstrinsik. Minuman soda merupakan salah satu minuman yang dapat menyebabkan perubahan warna pada resin komposit. Tujuan: Tujuan dari penelitian ini untuk meneliti perubahan warna resin komposit nanohibrida akibat perendaman dalam minuman soda. Metode: Metode yang digunakan pada penelitian ini adalah eksperimental laboratorik dengan menggunakan 100 spesimen resin komposit nanohibrida shade A3 berdiameter 5 mm dan tebal 2 mm. Sampel dibagi dalam 5 kelompok, masing-masing kelompok direndam dalam minuman yang berbeda, yaitu direndam dalam air mineral, soda lemon, soda strawberi, soda fruitpunch, dan soda jeruk selama 3, 7, 14 dan 21 hari, dalam suhu 37o C. Pengukuran perubahan warna menggunakan Spectrophotometer, Vita Easy Shade dengan metode CIEL*a*b*. Hasil: Hasil penelitian menunjukkan bahwa lama perendaman pada minuman soda berpengaruh terhadap perubahan warna resin komposit nanohibrida. Soda yang paling berpengaruh terhadap perubahan warna adalah soda strawberi dan soda fruitpunch. Namun perubahan warna yang terjadi secara umum masih dapat diterima secara klinis (∆E ≤ 3,3). Simpulan: Hasil penelitian ini menunjukkan bahwa lamanya waktu perendaman mempengaruhi perubahan warna pada resin komposit nanohibrida.